Bio-chemo-mechanics of thoracic aortic aneurysms. (March 2018) - Wagenseil, Jessica E.
Abstract: Most thoracic aortic aneurysms (TAAs) occur in the ascending aorta. This review focuses on the unique bio-chemo-mechanical environment that makes the ascending aorta susceptible to TAA. The environment includes solid mechanics, fluid mechanics, cell phenotype, and extracellular matrix composition. Advances in solid mechanics include quantification of biaxial deformation and complex failure behavior of the TAA wall. Advances in fluid mechanics include imaging and modeling of hemodynamics that may lead to TAA formation. For cell phenotype, studies demonstrate changes in cell contractility that may serve to sense mechanical changes and transduce chemical signals. Studies on matrix defects highlight the multi-factorial nature of the disease. We conclude that future work should integrate the effects of bio-chemo-mechanical factors for improved TAA treatment. Graphical abstract: Highlights: Most thoracic aortic aneurysms (TAAs) occur in the ascending aorta (AA). Bio-chemo-mechanical factors likely contribute to TAA susceptibility in the AA. Factors include solid and fluid mechanics, cell phenotype, and matrix composition. Multifactorial studies are needed to better understand and treat TAA.